The Role of Communities in Agrarian Conflict Resolution Based on Local Wisdom and Environmental Justice (Case Study of Widarapayung Emerging Land, Cilacap) - Faizal Nur Rachman; Ageng Widodo (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the role of local communities in agrarian conflict resolution in the emerging land area (Tanah Timbul) of Widarapayung, Cilacap, within the framework of local wisdom and environmental justice. Methodologically, the research employs a qualitative case study approach through in depth interviews with community leaders, farmers/fishers, village authorities, and relevant institutions; focus group discussions; participant observation; and document review. Data were analyzed thematically using source triangulation. The findings indicate that the community operates across three interrelated domains: (1) organizational strengthening as a space to build trust and channels of dialogue; (2) normative mediation that draws on the principles of maqaṣid al-syari’ah, ‘urf, and the ethics of hisbah to negotiate access rights, boundaries, and the governance of the emerging land; and (3) ecological practices rooted in local wisdom, such as gotong royong (mutual cooperation), prohibitions against overexploitation, and coastal vegetation rehabilitation, which foster co-management schemes and adaptive land-use arrangements. The integration of these three domains reduces conflict escalation, produces fairer benefit-sharing agreements, and strengthens the protection of coastal ecological functions. This study contributes to the literature on coastal agrarian conflicts by offering a community-based resolution model that is both contextual and replicable, and recommends strengthening collaboration among village institutions, civil society organizations, religious groups, and government actors within the framework of environmental justice.